The Role of Blockchain in Securing IoT Devices - Jibrin, Abubakar; Ishaq, Ashraf; Ahmed, Aliyu; Gadafi, Adamu Muhammad (Kwaghe International Journal of Engineering and Information Technology, 2025)
The proliferation of Internet of Things (IoT) devices has introduced unprecedented security challenges, including data breaches, unauthorized access, and the exploitation of centralized network vulnerabilities. Traditional security architectures struggle to provide robust protection due to the distributed and resource-constrained nature of IoT environments. Blockchain technology, with its decentralized ledger, cryptographic security, and smart contract functionality, presents a promising approach to mitigating these risks. By ensuring data integrity, enabling secure authentication, and facilitating trustless interactions among IoT devices, blockchain can enhance the overall security framework of IoT ecosystems. This paper critically examines the role of blockchain in securing IoT networks, outlining its key benefits, potential real-world applications, and associated limitations. While blockchain addresses fundamental IoT security concerns, challenges such as scalability, computational overhead, and integration complexity hinder widespread adoption. The study underscores the need for further research into optimizing blockchain protocols for IoT environments and explores potential advancements in hybrid security models.